1998
DOI: 10.1097/00005537-199802000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography in the Evaluation of the N0 Neck

Abstract: The presence of cervical lymph node metastasis in patients with head and neck cancer is associated with an unfavorable prognosis. Reports vary as to whether various conventional radiographic studies, such as computed tomography (CT) and magnetic resonance imaging, confer an advantage over physical examination in the patient without clinical findings of cervical metastasis (N0). Positron emission tomography (PET) is a functional imaging modality that has recently been used for head and neck neoplasms. The use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1
5

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 23 publications
0
47
1
5
Order By: Relevance
“…It is well known that nonspecific uptake in brown fat planes and muscle attachment sites ( Figure 2E) is a common cause of false-positive results (Engel et al, 1996;Kostakoglu et al, 1996;McGuirt et al, 1998). This false-positive feature has a critical impact on nodal staging of head and neck tumours (Helmberger et al, 1996;Myers et al, 1998;Hannah et al, 2002). The possibility of false-positive sites on 18 F-FDG PET alone also holds true in the postsurgical and postradiotherapy neck, where distortion of normal anatomy can further add to the complexity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that nonspecific uptake in brown fat planes and muscle attachment sites ( Figure 2E) is a common cause of false-positive results (Engel et al, 1996;Kostakoglu et al, 1996;McGuirt et al, 1998). This false-positive feature has a critical impact on nodal staging of head and neck tumours (Helmberger et al, 1996;Myers et al, 1998;Hannah et al, 2002). The possibility of false-positive sites on 18 F-FDG PET alone also holds true in the postsurgical and postradiotherapy neck, where distortion of normal anatomy can further add to the complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical lymph nodes are the most common site for tumour spread (Mendenhall et al, 1998;Ak et al, 2000), and this is a relatively common clinical presentation (Mendenhall et al, 1998;Ak et al, 2000). The presence or absence of cervical lymphadenopathy is of prognostic significance (Myers et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the patients without lymph node metastasis at presentation will subsequently manifest metastasis. Since removal of lymph nodes and/or radiation and chemotherapy can reduce emergence of occult metastasis, attempts to predict the patients in this category are made clinically (Kim et al, 1993;Myers et al, 1998). Currently, node-negative patients estimated to have a 20% or greater risk of metastasis often have surgical removal of draining lymph nodes and radiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is also impractical to use imaging techniques for cancer screening, since they are time-consuming and expensive. These techniques are typically used for confirmation due to their insensitivity for small lesions [6]. Studies have demonstrated that good positive-predictive values can be achieved by oral cancer tissue staining with toluidine blue [7,8].…”
Section: Current Oral Cancer Diagnostic and Screening Approachesmentioning
confidence: 99%